Productivity Characteristics Of Sorghum Varieties Under Water Shortage Conditions (Texas Journal of Agriculture and Biological Sciences, 2024)
The article presents the data obtained on the basis of the study of the yield characteristics of the Karabash, Massino, Samurai and Uzbek Pakana and Uzbek-18 varieties of sorghum under water deficit conditions. Among some physiological indicators studied under water shortage conditions, it was determined that the rate of height growth of the varieties, the expansion of the leaf surfaces, and the value of the net photosynthesis productivity change in different levels in the cross-section of the varieties, depending on their resistance levels